THE USE OF ICT IN "DISCRETE MATHEMATICS" METHODICAL SYSTEM OF EDUCATION FOR THE FORMATION OF INFORMATION COMPETENCE - E.V. Azadova (Kherson State University, 2012)
The article deals with the implementation of information and communication technologies in educational system of "Discrete Mathematics" as a way to formation of students' information competence.